Reproductive isolation between sympatric Anguilla japonica and Anguilla marmorata. Issue 5 (9th October 2017) - Chow, S.; Kurogi, H.; Yamamoto, T.; Tomoda, T.; Mochioka, N.; Shirotori, F.; Yoshinaga, T.; Ambe, D.; Okazaki, M.; Nagai, S.; Yanagimoto, T.
Abstract : Species‐specific restriction fragment length polymorphism in the intron of the androgen receptor gene ( ar5 ) was found in glass to silver‐stage individuals of Anguilla japonica ( n = 51) and A. marmorata ( n = 21). The sequence analysis of 16S rDNA from 328 anguillid leptocephali collected in the North Equatorial Current of the western North Pacific Ocean revealed the specimens to be A. japonica ( n = 194), A. marmorata ( n = 128), A. bicolor pacifica ( n = 5) and A. luzonensis ( n = 1). All leptocephali of A. japonica and A. marmorata were monomorphic and did not share an allele at the ar5 locus, indicating that the two species are reproductively isolated.